Dual‐Cure Coatings: Spiroorthoesters as Volume‐Controlling Additives in Thiol–Ene Reactions. Issue 4 (3rd April 2019) - Marx, Philipp; Romano, Angelo; Fischer, Roland; Roppolo, Ignazio; Sangermano, Marco; Wiesbrock, Frank
Abstract : Front Cover : In article number 1800627 by Marco Sangermano, Frank Wiesbrock, and co‐workers, bicyclic spiroorthoesters undergo volumetric expansion upon cationic (double) ring‐opening polymerization. They can be used as additives in polymerizations to control the shrinkage that conventional polymerizations exhibit; if the spiroorthoesters bear olefinic structural motifs, they can be covalently attached into thiol–ene networks, while the shrinkage/expansion can be tailored.